2014
DOI: 10.1007/s13246-013-0238-5
|View full text |Cite
|
Sign up to set email alerts
|

ACPSEM ROSG Oncology-PACS and OIS working group recommendations for quality assurance

Abstract: The Australasian College of Physical Scientists and Engineers in Medicine (ACPSEM) Radiation Oncology Specialty Group (ROSG) formed a series of working groups in 2011 to develop position papers for guidance of radiation oncology medical physics practice within the Australasian setting. These position papers are intended to provide guidance for safe work practices and a suitable level of quality control without detailed work instructions. It is the responsibility of the medical physicist to ensure that locally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Other studies used quantitative methods. (15,20) qualitative methods, (19) and mixed methods (qualitative and quantitative). (14) The aims of these studies were creating a national radiation oncology registry, (18) determining the level of compliance of clinical activities with a radiotherapy information system, (14) identifying deficiencies in treatment plans and radiotherapy simulation, (16) developing a patient's electronic chart, (17) and creating a web-based radiotherapy system.…”
Section: Radiotherapy Information Systemsmentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies used quantitative methods. (15,20) qualitative methods, (19) and mixed methods (qualitative and quantitative). (14) The aims of these studies were creating a national radiation oncology registry, (18) determining the level of compliance of clinical activities with a radiotherapy information system, (14) identifying deficiencies in treatment plans and radiotherapy simulation, (16) developing a patient's electronic chart, (17) and creating a web-based radiotherapy system.…”
Section: Radiotherapy Information Systemsmentioning
confidence: 99%
“…The results indicated that in addition to facilitating the reporting of outcomes, the system reduced the average time of documentation by physicians from 22 to 7 minutes per patient, and 92% of respondents were satisfied with the system. (22) Other research objectives were creating a filing system for radiotherapy, (21) developing a mock-up of a user interface to predict radiotherapy workflows, (2) determining the progress of information technology in the radiotherapy section, (15) providing guidance to achieve an appropriate level of quality control (19) and evaluation of experts' opinions about the use of DICOM-RT in radiotherapy. (20) In a research conducted by Mukai et al a filing system for radiotherapy department was created.…”
Section: Radiotherapy Information Systemsmentioning
confidence: 99%
See 3 more Smart Citations